Forecasting the Price of Broiler Eggs Using the Generalized Space-Time Autoregressive Method in 3 Regions with The Highest Egg Prices in East Java - Anwar, Ken Najwa Salsabila (Universitas Brawijaya, 2026)
Time series is the data that is compiled based on the time sequence. Not only time series data, but there is also some data that have a relationship between time and location, which is called space-time data. One of the analyses used in space-time data is Generalized Space-Time Autoregressive (GSTAR). This study applied the GSTAR method to create a model for the price of broiler eggs in Pamekasan Regency, Sampang Regency, and Sumenep Regency and also do the forecasting for the price of broiler eggs for the next 12 months. Modeling using GSTAR for the price of broiler eggs shows that all parameters are not significant. Therefore, changes in the prices of broiler eggs are not influenced by the price of broiler eggs from other regencies or prices from their regency. However, based on the MAPE and RMSE, the best model is GSTAR ( )I(1) with inverse distance weight. The RMSE and MAPE of the GSTAR ( )I(1) model with inverse distance weight are 1.565,85 and 4,68%. Keywords: broiler egg price, GSTAR, inverse distance weight, uniform weight, normalized cross-correlation weight.